Analysis of the demand and influencing factors of the family members of children with cardiovascular diseases in a certain hospital in Jinan (济南市某三甲医院心血管病患儿家属对居家医养护需求及影响因素分析) - MOU Xiao (牟啸) (中西医结合护理)
Objective To explore the demand of family members of children with cardiovascular diseases for home care and analyze the influencing factors. Methods A total of 198 family members of children with cardiovascular diseases from a certain hospital in Jinan, Shandong Province were investigated by using general information questionnaire and children's home care needs score questionnaire. Results Family members of children with cardiovascular diseases had a relatively high demand for professional nursing services. Activities of daily living (ADL), education background of family members, disease duration and knowledge of cardiovascular disease were the influencing factors of family members of children with cardiovascular disease (P<0. 01). Conclusion Family members of children with cardiovascular diseases have a great demand for home-based medical care. Efforts should be made to strengthen the home-based medical service training for family members, especially those with low education level, children with short disease duration, children with poor activities of daily living, and family members who do not know the relevant knowledge of cardiovascular diseases, so as to provide a more perfect care system for these people. (目的 探讨山东省济南市某三甲医院心血管病患儿家属对居家医养护需求现状, 并分析其影响因素。方法 采用一般资料调查表和患儿居家医养护需求评分表对整群抽取的198名来自山东省济南市某三甲医院的心血管病患儿家属进行问卷调查。结果 心血管病患儿家属对专业护理服务的需求相对较大。患儿日常生活活动能力、家属学历、患病病程、是否了解心血管病相关知识是心血管病患儿家属对居家医养护的需求水平的影响因素(P＜0. 01)。结论 心血管病患儿家属对居家医养护需求较大, 在为这类患儿出院时及出院后应该加强对家属的居家医疗服务培训, 尤其应该重点关注学历层次低、患病病程短、日常生活活动能力差的患儿、不了解心血管病相关知识的家属, 为这类人群提供更加完善的照护体系。)